An effective strategy to promote hematite photoanode at low voltage bias via Zr4+/Al3+ codoping and CoOx OER co-catalyst. (1st October 2019) - Subramanian, Arunprabaharan; Mahadik, Mahadeo A.; Park, Jin-Woo; Jeong, In Kwon; Chung, Hee-Suk; Lee, Hyun Hwi; Choi, Sun Hee; Chae, Weon-Sik; Jang, Jum Suk
Abstract: Herein, we report the surface treatment on Zr 4+ /Al 3+ codoped α-Fe2 O3 photoanode for high-performance photoelectrochemical water splitting. A high-temperature quenching exhibits the Zr 4+ /Al 3+ codoping in α-Fe2 O3 photoanode without damaging morphology. The presence of Zr 4+ /Al 3+ codoping shows a cathodic shift in onset potential, but lack of increment in photocurrent reveals the major role of passivation and the minimum doping effect of aluminum. Additionally, CoOx cocatalyst exhibits increment in photocurrent with the greater cathodic shift in onset potential than the pristine α-Fe2 O3 nanorods. The CoOx surface-reworked Zr 4+ /Al 3+ codoped α-Fe2 O3 photoanode displays the highest photocurrent of 1.5 mA/cm 2 at 1.23 V vs. RHE (76% increment over the pristine α-Fe2 O3 ) and 0.7 mA/cm 2 at 1.0 V vs. RHE (102% increment over the pristine α-Fe2 O3 ). The systematic characterization carried out using x-ray diffraction and scanning electron microscopy confirms that after Zr 4+ /Al 3+ codoping, and surface treatment, the crystalline structure, and morphology of the photoanodes remains unchanged. X-ray photoelectron spectroscopy confirmed the existence of Zr 4+ /Al 3+ codopants in the hematite nanostructure. The electrochemical properties of the photoanode suggest that Al 3+ and Zr 4+ codoping, as well as surface treatment with CoOx, cocatalyst lowers charge transfer resistance across the FTO/hematite interface, and hematite/electrolyte interface. This designs not only lowers onset potential but also offers the blueprint for the development of an efficient catalyst for solar water oxidation. Graphical abstract: CoOx surface-reworked Zr 4+ /Al 3+ codoped α-Fe2 O3 photoanode displays the 102% increment in PEC performance than pristine α-Fe2 O3 at 1.0 V vs. RHE.Image 1 Highlights: Zr 4+ /Al 3+ -codoped Fe2 O3 photoanode synthesized by hydrothermal method. CoOx co-catalyst improves the OER kinetics via surface reworking. Optimum photoanode exhibits 102% increase in photocurrent density than Fe2 O3 . The charge transfer mechanism in 6% Zr + 6% Al + 15 mM Co is also proposed.